Functional connectivity of emotional processing in depression - Carballedo, Angela; Scheuerecker, Johanna; Meisenzahl, Eva; Schoepf, Veronika; Bokde, Arun; Möller, Hans-Jürgen; Doyle, Myles; Wiesmann, Martin; Frodl, Thomas (Journal of affective disorders, 2011)
The aim of the study is to map a neural network of emotion processing and to identify differences in major depression compared to healthy controls. It is hypothesized that intentional perception of emotional faces activates connections between amygdala (Demir et al.), orbitofrontal cortex (OFC), anterior cingulate cortex (ACC) and prefrontal cortex (PFC) and that frontal-amygdala connections are altered in major depressive disorder (MDD). Fifteen medication-free patients with MDD and fifteen healthy controls were enrolled. All subjects were assessed using the same face-matching functional Magnetic Resonance Imaging (fMRI) task, known to involve those areas. Brain activations were obtained using Statistical Parametric Mapping version 5 (SPM5) for data analysis and MARSBAR for extracting of fMRI time series. Then data was analyzed using structural equation modeling (SEM). A valid model was established for the left and the right hemispheres showing a circuit involving ACC, OFC, PFC and AMY. The left hemisphere shows significant lower connectivity strengths in patients than controls, for the pathway that goes from AMY to the OF11, and a trend of higher connectivity in patients for the path that goes from the PF9 to the OF11. In the right hemisphere, patients show lower connectivity coefficients in the paths from the AMY to OF11, from the AMY to ACC, and from the ACC to PF9. By the contrary, controls show lower connectivity strengths for the path that goes from ACC to AMY. Functional disconnection between limbic and frontal brain regions could be demonstrated using structural equation modeling. The interpretation of these findings could be that there is an emotional processing bias with disconnection bilaterally between amygdala to orbitofrontal cortices and in addition a right disconnection between amygdala and ACC as well as between ACC and prefrontal cortex possibly in line with a more prominent role for the right hemisphere in emotion processing.